The Influence of Organizational Culture and Organizational Climate on Employee Performance at Halu Oleo University, Kendari, Southeast Sulawesi Province - Alfonsus Beo Say; Muhammad Makruf (Jurnal Wacana Ekonomi, 2025)
The organizational culture at Halu Oleo University, Kendari, Southeast Sulawesi Province, is still not optimal as expected, so this organizational culture has become a concern for progress.Halu Oleo University, Kendari, Southeast Sulawesi ProvinceThe purpose of the study itself is not to analyze, but to find out the results of the analysis, the results of the hypothesized calculations. The results of the study show that, the calculated t value for variable X1 (Organizational Culture) is 6.308 while the t table value for n = 75 is 1.993. So 6.308 > 1.993, it can be concluded that partially the organizational culture variable (X1) has an effect on Employee Performance (Y), the calculated t value for variable X2 (Organizational Climate) is 12.573 while the t table value for n = 75 is 1.993. So 12.573 > 1.993 can be concluded that partially the Organizational Climate variable (X2) has an effect on Employee Performance (Y), the calculated f value is 88.905 which is greater than the ftable value for n = 75 of 3.12 or 88.905 > 3.12 with a significance level of 0.00 because 0.00 < 0.05, so it can be said that Organizational Culture (X1) and Organizational Climate (X2) simultaneously together are able to explain Employee Performance (Y).